2016
DOI: 10.1186/s13601-016-0114-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of profilin on sensitisation profiles determined by cutaneous tests and IgE to major allergens in polysensitised patients

Abstract: BackgroundProfilin sensitisation is considered a diagnostic confounding factor in areas where patients are exposed to multiple pollens. The aim of this study is to assess pollen sensitisation profiles in adults and children and to evaluate, by means of component-resolved diagnosis (CRD) and skin prick testing (SPT), which pollens may be considered as risk factors of profilin sensitisation in order to establish the best diagnostic approach in polysensitised patients.MethodsA total of 231 pollen-allergic patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…Consistently with this finding, the multivariate analysis showed that the type of disease significantly contributed to sensitization to group 1 (Der p 1 and Der f 1) house dust mite allergens, whereas the severity of the disease significantly influenced sensitization to group 2 (Der p 2 and Der f 2) house dust mite allergens; sensitization to Lep d 2 was associated with both the type and severity of the disease. Similar relationships have been reported between various pollens and the type of respiratory disease [22, 26, 27]; however, to our knowledge, this is the first study showing a relationship between disease type/severity and house dust mite allergens. Although evidence regarding these specific relationships is still weak, consistent findings that specific antigens are associated with clinical characteristics of the respiratory disease strengthen the importance of using CRD to assess the sensitization profile of patients with respiratory allergy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistently with this finding, the multivariate analysis showed that the type of disease significantly contributed to sensitization to group 1 (Der p 1 and Der f 1) house dust mite allergens, whereas the severity of the disease significantly influenced sensitization to group 2 (Der p 2 and Der f 2) house dust mite allergens; sensitization to Lep d 2 was associated with both the type and severity of the disease. Similar relationships have been reported between various pollens and the type of respiratory disease [22, 26, 27]; however, to our knowledge, this is the first study showing a relationship between disease type/severity and house dust mite allergens. Although evidence regarding these specific relationships is still weak, consistent findings that specific antigens are associated with clinical characteristics of the respiratory disease strengthen the importance of using CRD to assess the sensitization profile of patients with respiratory allergy.…”
Section: Discussionsupporting
confidence: 85%
“…Another limitation of our results was the low prevalence of panallergens found in our study cohort. The presence of these allergens, which is commonly higher in other studies [20, 22, 27], has been considered a key benefit of CRD and may increase the differences between the two types of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It also correlated well with the ImmunoCAP ® system. A good agreement and correlation for some allergen components with the ImmunoCAP Immuno Solid-phase Allergen Chip (ISAC) microarray was revealed[ 66 - 68 ].…”
Section: Singleplex Immunoassays For Specific Ige To Allergen Componementioning
confidence: 99%
“…Profilin sensitization is a diagnostic confounding factor. A study assessed pollen sensitization profiles in adults and children and evaluated these sensitization by means of component‐resolved diagnosis (CRD, ADVIA‐Centaur) and skin prick testing (SPT) . In patients sensitized to profilin, the concordance between SPT and CRD is much lower than in those not sensitized to profilin.…”
Section: Diagnosismentioning
confidence: 99%